Urgensi Pemahaman Kontekstual Hadis (Refleksi terhadap Wacana Islam Nusantara) - Tasbih Tasbih (Al-Ulum, 2016)
This writing tries to show the importance of contextual understanding on hadith in order to response Islam Nusantara discourse. It is library research which takes contextual understanding on hadith and Islam Nusantara as its variables of research. The research result shown that contextual meaning is an approach which done, as an effort to analyze the meaning of hadith. it is done when there is inconsistency between the situation on a society or a certain time of decade. The hadith said that the leader should be taken from Quraisy tribe or the hadith about a nation will never find its prosperous when the leadership is given to woman are two examples which will get difficulties when it will be applied in Indonesia, as long as it is still understood textually. However, both do not find clashes when it is understood contextually. Therefore, all the Islam scientific are demanded to be ready in responding the actual problems on society life, especially in Indonesia archipelago, in order to reflect the elasticity of Islam teaching principle and method on mu’amalah and social relation issues.